Indexed Left Atrial Adipose Tissue Area Is Associated With Severity of Atrial Fibrillation and Atrial Fibrillation Recurrence Among Patients Undergoing Catheter Ablation - Sanghai, Saket R.; Sardana, Mayank; Hansra, Barinder; Lessard, Darleen M.; Dahlberg, Seth T.; Aurigemma, Gerard P.; Fitzgibbons, Timothy P.; McManus, David D. (Frontiers in Cardiovascular Medicine, 2018)
Background: Epicardial adipose tissue (EAT) has been associated with adverse left atrial (LA) remodeling and atrial fibrillation (AF) outcomes, possibly because of paracrine signaling. Objectives: We examined factors associated with a novel measure of EAT i.e. indexed LAEAT (iLAEAT) and its prognostic significance after catheter ablation (CA) of atrial fibrillation (AF). Methods: We performed a retrospective analysis of 274 participants with AF referred for CA. LAEAT area was measured from a single pre-ablation CT image and indexed to body surface area (BSA) to calculate iLAEAT. Clinical, echocardiographic data and 1-year AF recurrence rates after CA were compared across tertiles of iLAEAT. We performed logistic regression analysis adjusting for factors associated with AF to examine relations between iLAEAT and AF recurrence. Results: Mean age of participants was 60±10 years, 136 (49%) were women, mean BMI was 32 ± 9 kg/m2 and 85 (31%) had persistent AF. Mean iLAEAT was 0.82±0.53 cm2/m2. Over 12-months, 109 (40%) had AF recurrence. Participants in the highest iLAEAT tertile were older, had higher CHA2DS2VASC scores, more likely to be male, have greater LA volume, and were more likely to have persistent (vs. paroxysmal) type AF than participants in the lowest iLAEAT tertile (p for all <0.05). In regression analyses, iLAEAT was associated with higher odds of AF recurrence (OR= 2.93; 95% CI 1.34-6.43). Conclusions: iLAEAT can quantify LA adipose tissue burden using standard CT images. It is strongly associated with AF risk factors and outcomes, supporting the hypothesis that EAT plays a role in the pathophysiology of AF.